PENGARUH KOMITMEN ORGANISASI DAN BUDAYA KERJA TERHADAP DISIPLIN KERJA KARYAWAN PT.TRANS SUMATERA AGUNG MEDAN - Mathilda Tania; Imanuel Tarigan; Syawaluddin Syawaluddin (JURNAL BISNIS KOLEGA, 2020)
Abstract. PT. Trans Sumatra Agung Medan is: a company engaged in the field of Suzuki brand car dealers. The phenomenon that occurs in companies is: a decrease in employee work discipline so that it interferes with company operations. The problem of decreased work discipline at the company allegedly caused by problems with organizational commitment and work culture. The population in this study were all employees in the company, amounting to 43 people. Samples were taken with a saturated sampling technique in which all members of the population were used as samples. Thus the sample in this study amounted to 43 people. Simultaneous hypothesis test results show that simultaneously Organizational Commitment and Work Culture has a significant effect on the Work Discipline of the employees of PT Trans Sumatra Agung, Medan. Partially, Organizational Commitment has a significant effect on the Work Discipline of the employees of PT. Trans Sumatra Agung, Medan and the Work Culture has a significant effect on the Work Discipline of the employees of PT. Trans Sumatra Agung, Medan.Â Keywords: Organizational Commitment, Work Culture, Employee Discipline.